Patterns of sensitivity to a panel of drugs are highly individualised for undifferentiated/unclassified soft tissue sarcoma (USTS) in patient-derived orthotopic xenograft (PDOX) nude-mouse models. (7th February 2019) - Kawaguchi, Kei; Igarashi, Kentaro; Miyake, Kentaro; Kiyuna, Tasuku; Miyake, Masuyo; Singh, Arun S.; Chmielowski, Bartosz; Nelson, Scott D.; Russell, Tara A.; Dry, Sarah M.; Li, Yunfeng; Unno, Michiaki; et al.
Abstract: Undifferentiated/unclassified soft tissue sarcoma (USTS) is a recalcitrant disease; therefore, precise individualised therapy is needed. Toward this goal, we previously established patient-derived orthotopic xenograft (PDOX) models of USTS in nude mice. Here, we determined the extent of uniqueness of drug response in a panel on USTS PDOX models from 5 different patients. We previously showed that 3 of the 5 patients were resistant to doxorubicin (DOX) despite DOX being first-line therapy. Two weeks after orthotopic tumour implantation, PDOX mouse models were randomised into five groups: untreated control, DOX, gem-citabine/docetaxel (GEM/DOC), pazopanib (PAZ), temozolomide (TEM). Three PDOX cases were completely resistant to DOX. TEM had high efficacy for 4 USTS PDOX models, including DOX-resistant cases. GEM/DOC and PAZ were effective in three USTS PDOX. One case was completely resistant to TEM. Two cases were completely resistant to PAZ. The results showed the drug sensitivity pattern for each USTS PDOX was highly individualised and that at least one effective drug could be found for each. The PDOX model could be effective in precise individualised drug sensitivity testing which is especially important for heterogeneous cancers such as USTS, and can give the patient a greater chance to be treated with an effective drug.